3
$\begingroup$

Evaluate $$ \int \frac{\mathrm{d}x}{x\sqrt{x^2+x+1}} \cdotp $$

My attempt: $$ I = \int \frac{\mathrm{d}x}{x\sqrt{x^2+x+1}} = \int \frac{\mathrm{d}x}{x\sqrt{\left(x + \frac{1}{2}\right)^2 + \left( \frac{\sqrt{3}}{2} \right)^2}} $$

I thought completing the square would bring the integrand into some form, but it did not. Please help.

$\endgroup$
6
$\begingroup$

Hint: I know a way. The integral of form $$\int\frac{dx}{(x-n)^m\sqrt{ax^2+bx+c}}$$ could be solved by taking $x-n=1/t.$. If you do this, then the whole integral will change to a integral of form $\int\frac{P(x)dx}{\sqrt{ax^2+bx+c}}$. Try this. Tell me if you can do the last one or not.

$\endgroup$
3
$\begingroup$

First use the substitution $x=\frac{1}{t}$ to get $$\int \frac{\mathrm{d}x}{x\sqrt{x^2+x+1}} =-\int \frac{\mathrm{d}t}{\sqrt{1+t+t^2}}.$$ Now complete the squares and use a tan substitution.

$\endgroup$
2
$\begingroup$

For integrals of the form $$\dfrac1{(x+a)\sqrt{(x+b)^2+c^2}},$$

Choose $x+b= c \tan y,$ to reach at an integral of the form $$\dfrac1{A\cos y+B\sin y}$$

Now $A\cos y+B\sin y=\sqrt{A^2+B^2}\sin (y+\arctan \dfrac AB)=\sqrt{A^2+B^2}\cos(y-\arctan\dfrac AB)$

$\endgroup$
1
  • $\begingroup$ Very nice! As always from your side. + $\endgroup$ – Mikasa Aug 27 '18 at 6:39
1
$\begingroup$

Try $x=1/t$. The integrand reduces to a known form.

$\endgroup$
0
$\begingroup$

$$I=\class{steps-node}{\cssId{steps-node-1}{2}}{\displaystyle\int}\dfrac{1}{x\sqrt{\left(2x+1\right)^2+3}}\,\mathrm{d}x$$

Substitute $u=2x+1$

$$I=2{\displaystyle\int}\dfrac{1}{\left(u-1\right)\sqrt{u^2+3}}\,\mathrm{d}u$$

Substitute $u=\sqrt{3}\tan\left(v\right)$ $$I=2{\displaystyle\int}\dfrac{\sqrt{3}\sec^2\left(v\right)}{\left(\sqrt{3}\tan\left(v\right)-1\right)\sqrt{3\tan^2\left(v\right)+3}}\,\mathrm{d}v$$ $$I=2{\displaystyle\int}\dfrac{\tan^2\left(\frac{v}{2}\right)+1}{\left(1-\tan^2\left(\frac{v}{2}\right)\right)\left(\frac{2\cdot\sqrt{3}\tan\left(\frac{v}{2}\right)}{1-\tan^2\left(\frac{v}{2}\right)}-1\right)}\,\mathrm{d}v$$

Substitute $w=\tan\left(\dfrac{v}{2}\right)$

$$I=\class{steps-node}{\cssId{steps-node-2}{4}}{\displaystyle\int}\dfrac{1}{w^2+2\cdot\sqrt{3}w-1}\,\mathrm{d}w$$

$$I=4{\displaystyle\int}\dfrac{1}{\left(w+\sqrt{3}-2\right)\left(w+\sqrt{3}+2\right)}\,\mathrm{d}w$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.